Global approaches to social policy: A survey of analytical methods - Nicola Yeates (United Nations Research Institute for Social Development (UNRISD), 2018)
The broader question addressed by this paper is whether social policy can still be understood as the outcome of sociopolitical forces exclusively rooted in and playing out through domestic spheres of governance. This question points to deep-rooted and difficult analytical and methodological issues relating to the analysis of social and public policies, whether at national or transnational levels. Indeed, the delineation of border-spanning phenomena in relation to social policy raises several fundamental questions regarding received knowledge about the nation state, sovereignty and territorial autonomy embedded in models of social policy and development; the prioritization given to the study of single societies at the expense of comparative analyses capable of providing a rich source of data and theories for "developing" and "developed" worlds alike; and the "co-production" of social policy by combinations of intersecting and interacting national and transnational actors, institutions and forces. In emphasizing the promise of an analytical approach focused on the co-production of social policies, it opens up the path for a productive dialogue among methodological nationalists and methodological transnationalists in relation to social policy and development. Such a dialogue holds out of the promise of significant conceptual, theoretical, methodological and empirical advances that in turn are capable of profound insights into the sources, dynamics and consequences of greater interconnectivity and interdependence characteristic of the conditions of contemporary social policy development and change.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330